Urgensi Aneka Pendekatan dalam Kajian Islam: Dari Inter-Multidisiplin ke Transdisiplin Menurut Amin Abdullah - Abdul Haq, Moh Mansur (Medina-te : Jurnal Studi Islam, 2023)
Religion (Islam) is always seen with a single face, even though many multidimensional aspects of Islam need to be researched. In general, the study of Islam that is not comprehensive is caused by the weakness of Muslims in mastering the methodology, not the mastery of Islamic teaching material. A new paradigm is needed to review the Islamic thought pattern as a solution to the problems of the Ummah so that it will make religion multi-face. Religious phenomena humans must be seen through the angle of understanding historicity, but only through the normative teachings revelation. This research aims to revitalise different approaches in Islamic studies so that Islam can become a religion that focuses on rahmatan lil ‘âlamîn instead of la’natan lil ‘âlamîn. With qualitative research methods and a descriptive-analytic approach sourced from various literature and data obtained from several journal articles, books, and especially data sources related to research. The result is that through the urgency of various inter-multidisciplinary to transdisciplinary approaches that form a spider web, in the sense of being integrated and connected, Islamic messages can be contextualised and can become shâlih li kulli zamân wa al-makân, so that the religious science branch (Islam) will not feel enough with itself without wanting to touch and relate to other sciences (al-Muhâfadzoh 'alâ al-Qodîm al-Shôlih wa al-Akhdzu bi al-Jadîd al-Ashlâh).